Kualitas Nugget Secara Organoleptik Berdasarkan Variasi Konsentrasi Bahan Dasar Ampas Tahu Dan Penerapannya Dalam Pembelajaran IPA - Lia Marlianti Seren; Ruspeni Daesusi (PEDAGO BIOLOGI, 2018)
This study aims to determine the effect of various variations of the dregs' concentration of tofu at nuggets, instead of wheat flour. The assessed aspects associated with the organoleptic nature of nuggets include: color, texture, flavor, taste. The ratio of dregs of tofu used is a mixture of 0%, 20%, 40%, 60%, 80%, 100%. This experimental study used a questionnaire tool. From the results of the questionnaire, the data was processed by using Friedman test and then continued with Wilcoxon test using SPSS program to know the difference of organoleptic value of nuggets with variation of tofu dregs 20%, 40%, 60%, 80%, 100%. If it is compared with original nugget, The content of dregs of tofu 0%.The results of data analysis showed that each variation of nitrate concentration of tofu dregs influences organoleptic properties including texture, flavor, color and aroma. The maximum concentration of tofu dregs that is still acceptable by the community is nugget with treatment, with the composition of the ratio of wheat flour 40% and the tofu dregs 60%. Nugget with this level results in a difference with the original nuggets, but the difference is still within the tolerance limit on the flavor and aroma aspect.